Improving the quality of XAFS data. (29th May 2018) - Abe, Hitoshi; Aquilanti, Giuliana; Boada, Roberto; Bunker, Bruce; Glatzel, Pieter; Nachtegaal, Maarten; Pascarelli, Sakura
Abstract : A summary of the discussion on aspects of a XAFS experiment that affect data quality, held at the Q2XAFS Workshop Satellite to IUCr Congress 2017 on `Data Acquisition, Treatment, Storage – quality assurance in XAFS spectroscopy' is reported. Abstract : Following the Q2XAFS Workshop and Satellite to IUCr Congress 2017 on `Data Acquisition, Treatment, Storage – quality assurance in XAFS spectroscopy', a summary is given of the discussion on different aspects of a XAFS experiment that affect data quality. Some pertinent problems ranging from sources and minimization of noise to harmonic contamination and uncompensated monochromator glitches were addressed. Also, an overview is given of the major limitations and pitfalls of a selection of related methods, such as photon‐out spectroscopies and energy‐dispersive XAFS, and of increasingly common applications, namely studies at high pressure, and time‐resolved investigations of catalysts in operando . Advice on how to avoid or deal with these problems and a few good practice recommendations are reported, including how to correctly report results.